(untitled) (Ustozlar uchun, 2026)
Speaking skills are a crucial part of the IELTS exam. The article discusses effective methods for improving speaking skills in English. It focuses on communicative approaches, role plays, group activities, and the use of audio and video materials to enhance students’ speaking abilities. Creating opportunities for students to use the language freely and actively participate in communication is essential. The article is based on the research of Uzbek, English, and Russian scholars in this field. Although most of the students are non-native speakers they struggle speak, communicate, and maintain fluency. However, nowadays, there are many methods to improve speaking, for example, shadowing, watching films, learning new words, and learning answers before exams. Some students who do those exercises can not see progress. In this article, I will write about learning band 9 answers, and the shadowing technique. Also, why are students afraid of speaking in an exam because of grammar or lack of vocabulary?